Phylum Acanthocephala Kohlreuther, 1771 In: Zhang, Z.-Q. (Ed.) Animal biodiversity: An outline of higher-level classification and survey of taxonomic richness - Monks, Scott; Richardson, Dennis J. (Zootaxa, 2011)
-